К изучению жужелиц (Coleoptera, Carabidae) Крымской Яйлы - Мальцев, И.В.; Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1971)
In the Crimean mountain pasture 118 species of Carabidae are found (58 — on western and 106 on eastern pastures). The character of their distribution in main biotopes
of the pastures is studied as well as the connection of mountain pasture Carabidae populations with those of foothill and plain Crimea. The possible reasons are mentioned of
differences in faunistic composition of western and eastern pastures. The data are presented confirming the opinion on initial lack of forests in the Crimean mountain pasture.